Opioid maintenance therapy in Switzerland: an overview of the Swiss IMPROVE study (Swiss Medical Weekly, 2014)
BACKGROUND/AIMS: Switzerland’s drug policy model has always been unique and progressive, but there is a need to reassess this system in a rapidly changing world. The IMPROVE study was conducted to gain understanding of the attitudes and beliefs towards opioid maintenance therapy (OMT) in Switzerland with regards to quality and access to treatment. To obtain a “real-world” view on OMT, the study approached its goals from two different angles: from the perspectives of the OMT patients and of the physicians who treat patients with maintenance therapy. The IMPROVE study collected a large body of data on OMT in Switzerland. This paper presents a small subset of the dataset, focusing on the research design and methodology, the profile of the participants and the responses to several key questions addressed by the questionnaires. METHODS: IMPROVE was an observational, questionnaire-based cross-sectional study on OMT conducted in Switzerland. Respondents consisted of OMT patients and treating physicians from various regions of the country. Data were collected using questionnaires in German and French. Physicians were interviewed by phone with a computer-based questionnaire. Patients self-completed a paper-based questionnaire at the physicians’ offices or OMT treatment centres. RESULTS: A total of 200 physicians and 207 patients participated in the study. Liquid methadone and methadone tablets or capsules were the medications most commonly prescribed by physicians (60% and 20% of patient load, respectively) whereas buprenorphine use was less frequent. Patients (88%) and physicians (83%) were generally satisfied with the OMT currently offered. The current political framework and lack of training or information were cited as determining factors that deter physicians from engaging in OMT. About 31% of OMT physicians interviewed were ≥60 years old, indicating an ageing population. Diversion and misuse were considered a significant problem in Switzerland by 45% of the physicians. CONCLUSION: The subset of IMPROVE data presented gives a present-day, real-life overview of the OMT landscape in Switzerland. It represents a valuable resource for policy makers, key opinion leaders and drug addiction researchers and will be a useful basis for improving the current Swiss OMT model.